Kemandirian Belajar dan Hubungannya dengan Hasil Belajar Siswa Kelas V Sekolah Dasar Negeri - Nuraini, Nuraini; Halidjah, Siti; Pranata, Rio (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This study was conducted to determine the relationship between self-directed learning and cognitive learning outcomes among fifth-grade students at State Elementary School 03 Pontianak Kota. Fifth-grade students at the school as the population, while the sample involving all 28 students in class V C which is determined by using purposive sampling technique based on recommendation of the principal. Data collection employed indirect communication techniques through a research questionnaire and documentary study techniques using formative assessment results of students' cognitive learning in the subject of Integrated Science and Social Studies (IPAS) on the topic of